Water and environmental issues - Mohd. Asharuddin, Syazwani; Radin Mohamed, Radin Maya Saphira; Mohd Kamil, Nor Amani Filzah (Penerbit UTHM, 2018)
Water is a precious and finite part of the environment which is vital for socioeconomic development, sustainability of the environment and survival. Malaysia is fortunate that it is located in a humid tropical area rich in rainfall and water resources. The rapid economic growth of Malaysia in the past decades is also mainly attributed to its ability to exploit abundant natural resources including water. The exploitation of water resources is an important catalyst of economic growth but continuous exploitation without proper management and conservation may cause the depletion of water supplies, rendering water resources unsustainable. In recent years, water problems have escalated in Malaysia due to climate change, urbanization and population explosion. Therefore, effective water conservation, efficient waste water and sewage management integrated with recent technologies are important for fostering the tandem development of economic growth and the sustainability of environmental resources.